Migration – After A Year of Covid-19 - Nicoleta Luminita POPESCU (GROAZNICU); Oana Camelia IACOB; Cristi RACEANU; Magdalena ANTON (MUȘAT) (Communications of International Proceedings, 2021)
This article analyzes migration, starting from the impact of public policies generated by the pandemic COVID19. The purpose of the approach is to outline the dynamics of migration that we can expect as a result of the effects of the pandemic, as well as to analyze the political measures adopted to combat these effects. The article refers mainly to what happened in Romania by analyzing the data from 2019-2021, being important in the context in which the social, political, economic dynamics has been and is very high, since the onset of the pandemic. In order to analyze the data, we will use methods of descriptive analysis with which we will find out the negative effects associated with a pandemic on migration, but also if the political restrictions imposed had a positive impact in order to combat the pandemic.
Keywords: COVID-19; Migration; Public Policy; Descriptive Analysis; Economy.